Contribuição para o estudo dos Rhinotragini (Coleoptera, Cerambycidae). II. Revisão de Ommata White, 1855 - Santos-Silva, Antonio; Martins, Ubirajara R.; Clarke, Robin O.S. (Papéis Avulsos de Zoologia, 2010)
The genus Ommata is reviewed and divided into four genera: Ommata sensu strictu, Acatinga gen. nov. (type species Odontocera (?) maia Newman, 1841), Etimasu gen. nov. (type species Ommata cosmipes Peñaherrera-Leiva & Tavakilian, 2003) and Pyrpotyra gen. nov. (type species Ommata (Ommata) paradisiaca Tippmann, 1953). Five new species are described: Ommata nigricollis (Brazil, Espírito Santo), Ommata andina (Bolivia), Pyrpotyra pytinga (Brazil, Pará), P. capixaba (Brazil, Espírito Santo), and P. paraensis (Brazil, Pará). The following species were transferred from Ommata to the new genera, besides the type species: Acatinga boucheri (Tavakilian & Peñaherrera-Leiva, 2005), comb. nov.; A. gallardi (Peñaherrera-Leiva & Tavakilian, 2004), comb. nov.; A. quinquemaculata (Zajciw, 1966), comb. nov.; Pyrpotyra albitarsis (Galileo & Martins, 2010), comb. nov.